2020
DOI: 10.1002/adsc.202000900
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Formal Arylation of (7‐Aza)isatylidene Malononitriles with α′‐Alkylidene‐2‐cyclohexenones

Abstract: An asymmetric intermolecular Rauhut-Currier reaction of α'-alkylidene 2-cyclohexenones and (7-aza)isatinylidene malononitriles is realized under the double activation catalysis of natural quinine and 2-mercaptobenzoic acid, finally affording formal 3-arylated spiro (7-aza)oxindole derivatives in fair to excellent enantioselectivity after a tandem cyclization/aromatization process (up to 96% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In 2020, the same group also used a thiol as co‐catalyst, but to protect the β‐position of the endo ‐cyclic alkene, which allowed the formation of the spirocyclic compounds 139 (Scheme 40). [66] Various parameters were scrutinized such as the catalyst and the acid co‐catalyst, as well as the temperature and the solvent. These studies led to the optimized reaction conditions showed in Scheme 40 with the use of quinine cat‐29 a .…”
Section: Functionalization Of 6‐alkylidenecyclohex‐2‐onesmentioning
confidence: 99%
“…In 2020, the same group also used a thiol as co‐catalyst, but to protect the β‐position of the endo ‐cyclic alkene, which allowed the formation of the spirocyclic compounds 139 (Scheme 40). [66] Various parameters were scrutinized such as the catalyst and the acid co‐catalyst, as well as the temperature and the solvent. These studies led to the optimized reaction conditions showed in Scheme 40 with the use of quinine cat‐29 a .…”
Section: Functionalization Of 6‐alkylidenecyclohex‐2‐onesmentioning
confidence: 99%
“…Nevertheless, 2-cyclohexenone 43 showed much lower reactivity and enantioselectivity under similar catalytic conditions. The double activation system combining thiol C30 and quinine was further applied to the asymmetric intermolecular RC of α 0 -alkylidene 2cyclohexenones 59 and (7-aza)isatinylidene malononitriles 73 by generating the dienolate ion pair intermediates (Scheme 26) [82]. After releasing thiol C30, a deprotonation of the chiral RC adduct occurred with the of quinine, and the resultant dienolate intermediates proceeded through a Pinner-type cyclization/[1,3]-H shift reaction, finally affording the formal 3-arylated spiro(7-aza)oxindole derivatives 74 with fair to excellent enantioselectivity.…”
Section: Double Activation Catalysis Involving Thiolsmentioning
confidence: 99%
“…19 The direct a-functionalization via the Morita-Baylis-Hillman (MBH) reaction with some reports. [20][21][22][23][24] The b-position could be attacked by nucleophiles with Michael reaction as a classic synthesis strategy. [25][26][27][28][29][30] Except for a ′ , a, b-positions with good progress, the high regioselective of g-functionalization to tune efficiently has been achieved.…”
mentioning
confidence: 99%